OF C'KETZ ANTIFOULING LAMINATION STRENGTH AGAINST THE TIME OF THE TIMING OF THE WOOD BED - Fakhrul Rozi; Syarifuddin Syarifuddin; Ronald M. Hutauruk (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractShip treatment with regard to the quality of the ship. When coating on the surface of the ship's skin, it is predicted that an increase in the economic and technical life of the hull. The purpose of this study was to determine the modulus of elasticity of C'kets Antifouling coating on meranti mangrove wood for soaking time. The research method used was an experiment with a completely randomized design of 6 treatments and 3 replications. Analysis of modulus of elasticity using the ANOVA test. Comparison of elastic modulus between specimens coated with C'Ketz Antifouling and uncoated was 51.3% with not soaked, 118.2% with 30 days immersion and 45.1% with 60 days immersion (Fcount>Ftable = 24.378> 3.11).Key words :C’ketz Antifouling, Modulus of Elasticity, Merantiwood.